Upaya Meningkatkan Hasil Belajar Pada Mata Pelajaran Pkn Melalui Model Pembelajaran Jigsaw - Millizal Millizal (Faculty of Teacher Training and Education, University of Lampung, 2016)
The purpose of this research is to find out if the use of kind of classroom cooperative attitude type jigsaw even could jazz up the activity and of study result of the student of class XII IPS-1 public senior high schools 11 Bandar Lampung. Research the act of this class to be implemented within a notebook detailing the development 2 and on a notebook detailing the development consisting of 2 meetings. A subject of study was students graduate XII IPS-1 public senior high schools 11 Bandar Lampung as many as 34 students. The technique of the collection of data by the use of sheets of observation, the technique of a test and documentation of. Of the data analysis uses the technique descriptive of qualitative. The results of the study paper work showing that the activity of of students to study every cyrcle the increase.Tujuan penelitian ini adalah untuk mengetahui apakah penggunaan model pembelajaran kooperatif tipe jigsaw dapat meningkatkan aktivitas dan hasil belajar siswa kelas XII IPS-1 SMA Negeri 11 Bandar Lampung. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus dan pada masing-masing siklus terdiri dari 2 kali pertemuan. Subjek penelitian adalah siswa XII IPS-1 SMA Negeri 11 Bandar Lampung sebanyak 34 siswa. Teknik pengumpulan data dengan menggunakan lembar observasi, teknik tes dan dokumentasi. Analisis data menggunakan teknik deskriptif kualitatif. Hasil penelitian menunjukan bahwa aktivitas belajar siswa setiap siklusnya meningkat.Kata kunci: hasil belajar, jigsaw, pelajaran PKn